# algebra 116

posted by .

Rewrite the equation y = 5x – 2 as a function of x.
This problem is already a function of x. y = 5x - 2 as a function of x.

Rewrite the equation –x – 4y = 20 as a function of x.

Graph f(x) = –3x – 2.

Solve the system by graphing.

## Similar Questions

1. ### math

rewrite each equation as afunction of x.-3y+4y=11 Where are the equations?
2. ### Algebra

Rewrite the equation as a function -3x+4y=11 If you want to consider y as a function of x, then y = (1/4)(3x +11) One can also write x as a function of y. x = (1/3)(4y - 11)
3. ### Calculus urgent

For the intergral of -(x^2)/3 +6 interval [0,3] Rewrite it as a function of n using the right hand endpoint without any summation sign. can anyone help me start this problem out?
4. ### Math

How would you rewrite the equation y = 3x+1 as a function of x. Hmmm. It is written now as a function of x. Do you mean like this, where x is a function of y?
5. ### Algebra

rewrite as an equation as a function of x -3+4=11
6. ### Algebra 1

Rewrite the equation y = –3x + 5 as a function of x.
7. ### Algebra 1

Rewrite the equation y = –3x + 5 as a function of x.
8. ### Math

The graph of a quadratic function has vertex(3,-4) and passes through the point (4,1). Find the equation of the function in standard form. Rewrite the equation in general form. Could someone explain to me how to do this, just don't …
9. ### Math

The graph of a quadratic function has vertex(3,-4) and passes through the point (4,1). Find the equation of the function in standard form. Rewrite the equation in general form. Could someone explain to me how to do this, just don't …
10. ### algebra 1

rewrite the equation so that y is a function of x. 2x = -3y + 10

More Similar Questions

Post a New Question